Innovation in Qur'an Hadith Learning Media Through Audio Visual Media - Priyatno, Dwi; Taufik, Muhamad; Siregar, Syahruddin; Syafiuddin, Fauzan Azima; Guilin, Xie (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Education is very important for all humans. There are so many learning media available for teachers and students. Educators and students can use one of these media, one of which is audio visual media. However, educators and students have not been able to use this audio visual media properly. Which by applying this audio visual media students are easier to understand learning. Purpose. This study aims to find out how to use this audio visual media for learning Al Qur'an hadith. Method. This research method uses quantitative methods and in-depth interviews. The results of this study are to find out the existence of teachers who apply audio visual media in learning Qur'an hadith, and there is an increase in student learning outcomes after the teacher applies this audio visual media. Results. This study explains that the role of audio-visual media in learning is very important, especially in learning Qur'an hadith. Conclusion. Because the existence of audio-visual media is very helpful for teachers in learning Qur'an hadith so that students easily understand the lesson, and also improve student achievement.